Adamantylidene Addition to M3N@Ih‐C80 (M=Sc, Lu) and Sc3N@D5h‐C80: Synthesis and Crystallographic Characterization of the [5, 6]‐Open and [6, 6]‐Open Adducts. Issue 27 (24th March 2017) - Yamada, Michio; Abe, Tsuneyuki; Saito, Chiharu; Yamazaki, Toshiki; Sato, Satoru; Mizorogi, Naomi; Slanina, Zdenek; Uhlík, Filip; Suzuki, Mitsuaki; Maeda, Yutaka; Lian, Yongfu; Lu, Xing; et al.
Abstract: Additions of adamantylidene (Ad) to M3 N@ Ih ‐C80 (M=Sc, Lu) and Sc3 N@ D 5 h ‐C80 have been accomplished by photochemical reactions with 2‐adamantyl‐2, 3′‐[3 H ]‐diazirine (1 ). In M3 N@ Ih ‐C80, the addition led to rupture of the [6, 6]‐ or [5, 6]‐bonds of the Ih ‐C80 cage, forming the [6, 6]‐open fulleroid as the major isomer and the [5, 6]‐open fulleroid as the minor isomer. In Sc3 N@ D 5 h ‐C80, the addition also proceeded regioselectively to yield three major isomeric Ad mono‐adducts, despite the fact that there are nine types of C−C bonds in the D 5 h ‐C80 cage. The molecular structures of the seven Ad mono‐adducts, including the positions of the encaged trimetallic nitride clusters, have been unambiguously determined through single‐crystal XRD analyses. Furthermore, results have shown that stepwise addition of Ad to Lu3 N@ Ih ‐C80 affords several Ad bis‐adducts, two of which have been isolated and characterized. The X‐ray structure of one bis‐adduct clearly revealed that the second Ad addition took place at a [6, 6]‐bond close to an endohedral metal atom. Theoretical calculations have also been performed to rationalize the regioselectivity. Abstract : Metallofullerene derivatization : Mono‐ and bis‐adamantylidene adducts of metallofullerenes M3 N@ Ih ‐C80 (M=Sc, Lu) and Sc3 N@ D 5 h ‐C80 have been prepared by photochemical reactions with 2‐adamantyl‐2, 3′‐[3 H ]‐diazirine (see graphic). The addition sites have been determined by single‐crystal X‐ray diffraction analysis.